Effects of the epidermal growth factor receptor inhibitor, gefitinib, on lipid and hyaluronic acid synthesis in cultured HaCaT keratinocytes. Issue 6 (11th February 2022) - Oh, Jang‐Hee; Hur, Woojune; Li, Na; Jo, Seong Jin
Abstract: Epidermal growth factor receptor inhibitors (EGFRIs) are widely used for treating various cancers, including lung, colon, head and neck cancers. However, EGFRIs have unique dermatological side effects, including acneiform eruption, dry skin, paronychia and pruritus. In this study, we investigated the molecular changes induced by an EGFRI, gefitinib, in the expression of lipogenic enzymes and hyaluronic acid (HA) regulatory proteins in HaCaT keratinocytes, and whether EGF restored these changes. HaCaT cells were treated with gefitinib, with or without EGF, and treated with tumor necrosis factor α (TNFα) for inducing an inflammatory response. The mRNA and protein expression was analyzed by real‐time RT‐PCR, enzyme‐linked immunosorbent assay (ELISA) and western blotting. Gefitinib enhanced the TNFα‐induced expression of C‐C motif chemokine ligand 2 (CCL2), CCL5 and C‐X‐C motif chemokine ligand 10 (CXCL10), and the expression of TNFα in HaCaT cells, while EGF restored these changes. At a similar concentration range, gefitinib reduced the mRNA and/or protein expression of various lipogenic enzymes for fatty acid, cholesterol and ceramide synthesis, except acidic sphingomyelinase. Gefitinib suppressed the mRNA and protein expression of HA synthase 2 (HAS2), HAS3, cluster of differentiation 44 (CD44), hyaluronidase 1 (HYAL1) and HYAL2, except the mRNA expression of HYAL1. EGF restored the changes induced by gefitinib, except for the mRNA expression of fatty acid synthase (FASN) and elongation of very long‐chain fatty acid protein (ELOVL) 6. In conclusion, EGFRIs suppress lipogenesis and HA metabolism, which may contribute to adverse dermatological effects, including barrier function impairment in cancer patients treated with EGFRIs.